Glutamate dehydrogenase is differentially regulated in seeded and parthenocarpic tomato fruits during crop development and postharvest storage - Tsilikochrisos, Georgios; Tsaniklidis, Georgios; Delis, Costas; Nikoloudakis, Nikolaos; Aivalakis, Georgios (My University, 2015)
© 2014 Elsevier B.V. Cherry tomatoes are more susceptible than larger fruit varieties to producing auxin-induced parthenocarpic fruits indistinguishable from seeded fruits in most organoleptic characteristics. In this study, the effects of auxin-induced parthenocarpy and of the short-term cold storage on the expression of GDH genes, one of the main regulatory enzymes of nitrogen metabolism, were examined. Seeded and parthenocarpic fruits exhibited differences in the pattern of expression of the genes coding for α- and β-subunits of GDH during fruit development. Short-term cold storage at 5. °C significantly increased transcript accumulation of GDH genes, while storage at 10. °C for five days mostly caused a reduction in the expression of the genes in both fruit types. Finally, no significant differences between the two fruit types were detected in the localization of GDH protein and GDH enzyme activity.
Keywords: Cherry tomato; Glutamate dehydrogenase; Immunolocalization; Parthenocarpy; Postharvest